Dapagliflozin Reduces Apoptosis of Diabetic Retina and Human Retinal Microvascular Endothelial Cells Through ERK1/2/cPLA2/AA/ROS Pathway Independent of Hypoglycemic - Hu, Yuxin; Xu, Qian; Li, Hongxue; Meng, Ziyu; Hao, Ming; Ma, Xuefei; Lin, Wenjian; Kuang, Hongyu (Frontiers in Pharmacology, 2022)
Introduction: It is known that the metabolic disorder caused by high glucose is one of pathogenesis in diabetic retinopathy (DR), the leading cause of blindness, due to the main pathological change of apoptosis of endothelial cells (ECs). In previous studies, the potential impact of sodium glucose cotransporter-2 (SGLT-2), whose inhibitors slow the progression of DR, has not been elucidated. The purpose of the presented study was to explore the effect of SGLT-2 inhibitors dapagliflozin (DAPA) on apoptosis of diabetic mice retina and human retinal microvascular endothelial cells (HRMECs), examine the effects of dapagliflozin on HRMECs metabolism, and explore the molecular processes that affect DR. Methods and Results: The eyeballs of male streptozotocin (STZ)-induced diabetic C57BL/6N mice were evaluated. C57BL/6N mice were divided into control group (CON), diabetic untreated group (DM), diabetic dapagliflozin treatment group (DM+DAPA) and diabetic insulin treatment group (DM+INS). Hematoxylin-Eosin (HE) staining was performed to observe the pathological structure of the mice retina, and TUNEL staining to detect apoptosis of mice retinal cells. In vitro, DCFH-DA and western blot (WB) were used to evaluate ROS, Bcl-2, BAX, cleaved-caspase 3 in HRMECs and metabolomics detected the effect of dapagliflozin on the metabolism of HRMECs. And then, we performed correlation analysis and verification functions for significantly different metabolites. In vivo, dapagliflozin reduced the apoptosis of diabetic mice retina independently of hypoglycemic. In vitro, SGLT-2 protein was expressed on HRMECs. Dapagliflozin reduced the level of ROS caused by high glucose, decreased the expression of cleaved-caspase3 and the ratio of BAX/Bcl-2. Metabolomics results showed that dapagliflozin did not affect the intracellular glucose level. Compared with the high glucose group, dapagliflozin reduced the production of arachidonic acid (AA) and inhibited the phosphorylation of ERK1/2, therefore, reducing the phosphorylation of cPLA2, which is a key enzyme for arachidonic acid release. Conclusion: Collectively, results unearthed for the first time that dapagliflozin reduced apoptosis of retina induced by DM whether in vivo or in vitro. Dapagliflozin did not affect the glucose uptake while mitigated intracellular arachidonic acid in HRMECs. Dapagliflozin alleviated HRMECs apoptosis induced by high glucose through ERK/1/2/cPLA2/AA/ROS pathway.